Globally elevated chemical weathering rates beneath glaciers - Li, Xiangying; Wang, Ninglian; Ding, Yongjian; Hawkings, Jon R.; Yde, Jacob C.; Raiswell, Robert; Liu, Jintao; Zhang, Shiqiang; Kang, Shichang; Wang, Rongjun; Liu, Qiao; Liu, Shiyin; et al. (Nature Communications, 2022)
Physical erosion and chemical weathering rates beneath glaciers are expected to increase in a warming climate with enhanced melting but are poorly constrained. We present a global dataset of cations in meltwaters of 77 glaciers, including new data from 19 Asian glaciers. Our study shows that contemporary cation denudation rates (CDRs) beneath glaciers (2174 +/- 977 Sigma*meq(+) m(-2) year(-1)) are similar to 3 times higher than two decades ago, up to 10 times higher than ice sheet catchments (similar to 150-2000 Sigma*meq(+) m(-2) year(-1)), up to 50 times higher than whole ice sheet means (similar to 30-45 Sigma*meq(+) m(-2) year(-1)) and similar to 4 times higher than major non-glacial riverine means (similar to 500 Sigma*meq(+) m(-2) year(-1)). Glacial CDRs are positively correlated with air temperature, suggesting glacial chemical weathering yields are likely to increase in future. Our findings highlight that chemical weathering beneath glaciers is more intense than many other terrestrial systems and may become increasingly important for regional biogeochemical cycles.